The role of Chinese products demand and supply in reducing market cost and improving technological performance: Empirical evidence from South Africa, Nigeria, and Egypt - Oluwole Nurudeen Omonijo; Zhang Yunsheng (Cogent Business & Management, 2023)
This study was conducted through an experimental study design. Our research question focuses on; (1) how Chinese products have reduced market costs in South Africa, Nigeria, and Egypt? (2) What impact do Chinese products have on the technology development process of the selected countries? (3) Which factors influence the expansion of Chinese products in the international market and how does primary research provide recommendation for using Chinese products to reduces market cost and improve technological performance. 279 responses were collected from the respondent in the selected countries to examine the performance of Chinese products. SPSS statistics software was used to analyze data using snowballing method to access the participants. Result on regression and correlation tests show that the number of Chinese products in the market positively predicted the market price. Technology performances were found to negatively impacts the supply of Chinese products. Our findings make a critical contribution to the existing theories on technology innovation, performance management, and product pricing. More specifically, (1) The increasing supply of Chinese products negatively affects the performance of technology in Africa; (2) A low level of technology adoption in the African market negatively impacts technology performance and technical performance is highly correlated with the availability of Chinese products;(3) The increase in Chinese products contributed to lower market prices. Our findings further suggest the increased demand and supply of Chinese products will adversely affect technology performance. Therefore, this study recommend that African leaders empower the youth to increase their exposure to Chinese technology.
Keywords: 650; Chinese products; Egypt; market costs; Nigeria; South Africa; technological performance